A CFD simulation study of boiling mechanism and BOG generation in a full-scale LNG storage tank. (12th July 2018) - Saleem, Abdullah; Farooq, Shamsuzzaman; Karimi, Iftekhar A.; Banerjee, Raja
Highlights: A maiden rigorous CFD simulation of a full-scale LNG storage tank gives insights of flow dynamics and boiling phenomena. The static pressure of the liquid affects the transient BOG generation rate, but the steady state value is unaffected. ∼2.8 K critical wall superheat required for nucleate boiling in LNG is unattainable in an insulated full-scale storage tank. Abstract: Despite heavy insulation, the unavoidable heat leak from the surroundings into an LNG (Liquefied Natural Gas) storage tank causes boil-off-gas (BOG) generation. A comprehensive dynamic CFD simulation of an onshore full-scale LNG tank in a regasification terminal is presented. LNG is approximated as pure methane, the axisymmetric VOF (Volume of Fluid) model is used to track the vapour-liquid interface, and the Lee model is employed to account for the phase change including the effect of static pressure. An extensive investigation of the heat ingress magnitude, internal flow dynamics, and convective heat transfer gives useful insights on the boiling phenomena and a reliable quantification of the BOG. Surface evaporation is the governing boiling mechanism and nucleate boiling is unlikely with proper insulation. The critical wall superheat marking the transition from surface evaporation to nucleate boiling is estimated as 2.5–2.8 K for LNG.